2015
DOI: 10.1021/acsnano.5b00042
|View full text |Cite
|
Sign up to set email alerts
|

The One Year Fate of Iron Oxide Coated Gold Nanoparticles in Mice

Abstract: Safe implementation of nanotechnology and nanomedicine requires an in-depth understanding of the life cycle of nanoparticles in the body. Here, we investigate the long-term fate of gold/iron oxide heterostructures after intravenous injection in mice. We show these heterostructures degrade in vivo and that the magnetic and optical properties change during the degradation process. These particles eventually eliminate from the body. The comparison of two different coating shells for heterostructures, amphiphilic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
185
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(194 citation statements)
references
References 62 publications
9
185
0
Order By: Relevance
“…The tendency of accumulation and hence slow clearance of SPIONs from the liver of mice after cell death is similar to the fate of free particles systemically injected in mice. 36 The spleen has very short relaxation time baseline values, and no further reduction was observed until the last imaging day in the case of free SPIONs (Fig. 5).…”
Section: Mri Complementary To Blimentioning
confidence: 90%
See 2 more Smart Citations
“…The tendency of accumulation and hence slow clearance of SPIONs from the liver of mice after cell death is similar to the fate of free particles systemically injected in mice. 36 The spleen has very short relaxation time baseline values, and no further reduction was observed until the last imaging day in the case of free SPIONs (Fig. 5).…”
Section: Mri Complementary To Blimentioning
confidence: 90%
“…Recently, the long term in vivo fate of different hybrids of SPIONs with gold nanoparticles has been established after directly injecting the particles in the blood stream of mice which revealed a predominant accumulation of particles in liver and spleen for longer periods of time. 36 In similar studies, the accumulation and metabolism of particles in the liver and spleen and loss of magnetic characteristics as a function of their surface coating, inner core and formation of protein corona was evaluated. [37][38][39][40] The electron paramagnetic resonance (EPR) based measurements of iron oxide nanocubes showed their considerable elimination from liver on day 7 post administration, whereas half of the proportion of particles stored in the spleen was still detected on day 7 post injection.…”
Section: Mri Complementary To Blimentioning
confidence: 99%
See 1 more Smart Citation
“…It was revealed that the initial surface properties have impact on the degradability and on the kinetics of elimination of magnetic iron and gold from liver and spleen. [376] Overall, although gold offers a lot of advantages for MNP, there are some difficulties that should overcome. The direct coating of iron oxide with gold is hard due the dissimilarity in the nature of the two crystalline surfaces making the coating to be weak which can be overcome by using TiO 2 as a bridging material.…”
Section: Gold Coatingmentioning
confidence: 99%
“…Au-NPs are known to primarily accumulate in the organs of the RES (e.g., liver) and show slow clearance over several months. 37,38 Therefore, this persistent retention could result in chronic toxicity within these tissues. In addition, degradation of Au-NPs could result in formation of smaller particles that are known to be toxic, as previously mentioned.…”
Section: Gold and Silver Npsmentioning
confidence: 99%